Vernacularizing Jainism: The Dharmapariksa by Manohardas - De Jonckheere, Heleen (Religions of South Asia, 2023)
This article argues that the religious and social developments of seventeenth-century Jain communities in northern India can be characterized as vernacularization. This is a process in which religious expression turns towards the quotidian, the local and the practical, and is strongly intertwined with vernacular literature and art. The article makes its argument by discussing the Dharmapariksa-bhasa by the Digambara author Manohardas (seventeenth century). This so-far unstudied text is an Old Hindi version of Amitagati’s Sanskrit Dharmapariksa (eleventh century) which criticizes by means of comical narration Brahmanical myths and beliefs. Presenting selections from this text, the article will highlight the intricate ways by which Manohardas’s bhasa reframes the Dharmapariksa to express the complexity that is vernacular Jainism. This involves emphasizing the spiritual-mystical interpretation of Jainism that was in vogue, but also drawing attention to the religious praxis of Jains and their others. The transposition into the northern Indian vernacular idiom suggests the role literary language played in vernacularizing Jainism. The discussions in the article present a Jainism that, while reflecting on its own tradition, defines itself in terms of the everyday regional religious environment of northern India.